2005
DOI: 10.1038/sj.cdd.4401766
|View full text |Cite
|
Sign up to set email alerts
|

The role of CAP3 in CD95 signaling: new insights into the mechanism of procaspase-8 activation

Abstract: Formation of the CD95 (APO-1/Fas) death inducing signaling complex (DISC) plays a central role in CD95 signaling. Previously, CD95 DISC composition was analyzed by twodimensional gel electrophoresis and four major cytotoxicityassociated proteins (CAP1-4) were found. CAP1 and CAP2 were defined to be unmodified and phosphorylated FADD, respectively. CAP4 was identified as procaspase-8a. CAP3, however, has remained elusive. In this study, we demonstrate that CAP3 is an intermediate of procaspase-8 processing. CAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
3
17
1
Order By: Relevance
“…This also fits to our previous studies of caspase-8 prodomain generation at the DISC. 13 The analysis of procaspase-8 and -10 processing in the lysates at later time points after CD95 stimulation further supported our findings ( Figure 2). Indeed, the intermediate procaspase-10 cleavage product increased up to 40% of the total procaspase-10 amounts over the first 30 min following CD95 stimulation (Figure 2a), while the p43/p41 levels of procaspase-8 always remained below 20% (Figure 2b).…”
Section: Resultssupporting
confidence: 87%
“…This also fits to our previous studies of caspase-8 prodomain generation at the DISC. 13 The analysis of procaspase-8 and -10 processing in the lysates at later time points after CD95 stimulation further supported our findings ( Figure 2). Indeed, the intermediate procaspase-10 cleavage product increased up to 40% of the total procaspase-10 amounts over the first 30 min following CD95 stimulation (Figure 2a), while the p43/p41 levels of procaspase-8 always remained below 20% (Figure 2b).…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, it has been shown that CD95 DISC formation at the membrane peaks minutes after stimulation and that the amount of the active CD95 DISC is markedly reduced 1 h after stimulation (21). The kinetics of DISC formation contradict our results (Fig.…”
Section: Cd95 Stimulation With Different Concentrations Of Lz-cd95l Rcontrasting
confidence: 56%
“…This processing occurs at Asp residues located between the prodomain and the large and the small catalytic subunits (Figure 2). 30,34 We have shown recently that cleavage between the prodomain and the large and the small catalytic subunits occurs simultaneously, though there is a preference towards a cleavage between the large and small catalytic subunits. 35 This processing results in the generation of a number of the cleavage products, including p43/p41, p26/ p24, CAP3, p30, p18 and p10 (Figure 2).…”
Section: Procaspase-8 and Its Activation At The Discmentioning
confidence: 99%
“…35 This processing results in the generation of a number of the cleavage products, including p43/p41, p26/ p24, CAP3, p30, p18 and p10 (Figure 2). [34][35][36][37] At the first cleavage step, the N-terminal p43/p41 and the C-terminal p30 cleavage products are generated. Importantly, these cleavage products already possess catalytic activity.…”
Section: Procaspase-8 and Its Activation At The Discmentioning
confidence: 99%